Cardiovascular Involvement in Pediatric Laminopathies. Report of Six Patients and Literature Revision - Baban, Anwar; Cicenia, Marianna; Magliozzi, Monia; Gnazzo, Maria; Cantarutti, Nicoletta; Silvetti, Massimo Stefano; Adorisio, Rachele; Dallapiccola, Bruno; Bertini, Enrico; Novelli, Antonio; Drago, Fabrizio (Frontiers in Pediatrics, 2020)
Lamin A/C (LMNA) encodes for two nuclear intermediate filament proteins. Mutations in LMNA cause a highly heterogeneous group of diseases predominantly affecting striated and cardiac muscles, adipose tissue and peripheral nerves. Laminopathies lead to muscular or cardiac disease, lipodystrophy syndromes, peripheral neuropathy, and accelerated aging disorders. Cardiac involvement includes progressive arrhythmias (brady/tachyarrhythmias, SCD). Furthermore, cardiomyocyte damage often progresses into dilated cardiomyopathy (DCM), rarely described in pediatric age group. Neuromuscular manifestations are even rarer in children. We reported on 6 pediatric patients with LMNA mutations: #1 operated for aortic coarctation, non compact left ventricle, atrial fibrillation preceding the diagnosis of DCM; #2 operated for VSD, developed after years malignant arrhythmias preceding the progression to DCM (left ventricular non compaction with LV dysfunction); # 3 with ectopic atrial tachycardia as first manifestation of a DCM. # 4 and #5 had no major arrhythmic events but only dilated ascending aorta, mildly dilated LV with mild hypertrabeculation of the lateral wall and a normally functioning but dilated left ventricle respectively, #6 showed aortic coarctation, supraventricular tachycardia. Paroxysmal AF occurred in #1,2,3 (50% of cases). Our series highlight the coexistence of congenital heart defects (CHD) and aortic involvement with laminopathies in 4 of our patients: consisting of aortic coarctation (2 pt), aortic root dilatation (1 pt) and ventricular septal defect (1 pt). Aortopathy has rarely so far described in association to LMNA variants but only in adults. This is the first report in the pediatric setting and no associations with CHD have been previously described.